2006
DOI: 10.1523/jneurosci.3741-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Response Inhibition in a Stop-Signal Task: Neural Correlates Independent of Signal Monitoring and Post-Response Processing

Abstract: Execution of higher cortical functions requires inhibitory control to restrain habitual responses and meet changing task demands. We used functional magnetic resonance imaging to show the neural correlates of response inhibition during a stop-signal task. The task has a frequent "go" stimulus to set up a pre-potent response tendency and a less frequent "stop" signal for subjects to withhold their response. We contrasted brain activation between successful and failed inhibition for individual subjects and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
215
2
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 518 publications
(250 citation statements)
references
References 62 publications
25
215
2
8
Order By: Relevance
“…This finding underscores the importance of studying the basis of failed inhibition, unlike previous studies. Functioning was notably altered in frontal inhibition-centers including the bilateral IFG/insula and the right SMA/ACC (Aron et al, 2003; Aron & Poldrack, 2006; Li et al, 2006), which signal the basal ganglia to suppress a motor response via projections to the subthalamic nucleus (Aron, 2011; Congdon et al, 2010; Levy & Wagner, 2011; Majid et al, 2013; Rubia et al, 2001). The LOW group exhibited significant hyperactivation of the SMA/ACC, whereas the HIGH group exhibited striking hypoactivation of this network, possibly due in part to atrophy of the left globus pallidus, which correlated with greater hypoactivation of the right IFG/ insula and SMA/ACC.…”
Section: Discussionmentioning
confidence: 99%
“…This finding underscores the importance of studying the basis of failed inhibition, unlike previous studies. Functioning was notably altered in frontal inhibition-centers including the bilateral IFG/insula and the right SMA/ACC (Aron et al, 2003; Aron & Poldrack, 2006; Li et al, 2006), which signal the basal ganglia to suppress a motor response via projections to the subthalamic nucleus (Aron, 2011; Congdon et al, 2010; Levy & Wagner, 2011; Majid et al, 2013; Rubia et al, 2001). The LOW group exhibited significant hyperactivation of the SMA/ACC, whereas the HIGH group exhibited striking hypoactivation of this network, possibly due in part to atrophy of the left globus pallidus, which correlated with greater hypoactivation of the right IFG/ insula and SMA/ACC.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that these associations were only significant at the uncorrected (i.e., p < 0.05) alpha level and, as such, should be considered tentative until replicated. Although past research has emphasized the role of the right inferior frontal gyrus in response inhibition (31), a number of studies have since demonstrated bilateral activation of the inferior frontal gyrus to response inhibition cues (32, 33). Similarly, although the insula has not been emphasized in the response inhibition literature, a recent meta-analysis demonstrated that insula is central to the brain's response to inhibition cues (14).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the intention to forget rather than remember neutral pictures produces greater functional MRI activation in only a small region of right lingual gyrus, the intention to forget rather than remember negative pictures leads to increased activation across a distributed network that includes middle frontal gyrus, middle temporal gyrus, parahippocampal gyrus, precuneus and cuneus in the right hemisphere, and lingual gyrus in both hemispheres (Nowicka, Marchewka, Jednorog, Tacikowski, & Brechmann, 2011). Because some of the brain areas that form this extensive neural network are implicated in visual selective attention (Kastner & Ungerleider, 2000), memory updating (Picard & Strick, 2001), and inhibition (Li, Huang, Constable, & Sinha, 2006), these findings suggest that more effort is expended to intentionally forget negative pictures than neutral pictures. Importantly, this additional effort is evinced in increased frontal activations even when the magnitude of the directed forgetting effect does not differ for negative and neutral items (Yang et al, 2012), arguing that similar behavioural outcomes may be underscored by dissimilar neural and cognitive processes.…”
Section: Discussionmentioning
confidence: 99%